2006
DOI: 10.1007/s00134-006-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inspired oxygen fraction on alveolar derecruitment in acute respiratory distress syndrome

Abstract: In mechanically ventilated patients with ALI the breathing of pure oxygen leads to derecruitment, which is prevented by high PEEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 30 publications
0
50
0
5
Order By: Relevance
“…Moreover, low tidal volume ventilation was lung-protective within 20 hrs of ovine fecal peritonitis (45) and in patients with acute respiratory distress syndrome despite increased FiO 2 levels (46). Furthermore, Aboab et al (47) recently demonstrated in patients with acute lung injury that high PEEP levels (about 15 cm H 2 O) together with low tidal volumes prevented alveolar derecruitment induced by 100% oxygen. Finally, the peritonitis per se may have attenuated any putative toxicity of 100% oxygen: Both reduced and increased sensitivities to hyperoxia were reported in animals challenged with lipopolysaccharide, oleic acid, and gastric juice aspiration (48 -50).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, low tidal volume ventilation was lung-protective within 20 hrs of ovine fecal peritonitis (45) and in patients with acute respiratory distress syndrome despite increased FiO 2 levels (46). Furthermore, Aboab et al (47) recently demonstrated in patients with acute lung injury that high PEEP levels (about 15 cm H 2 O) together with low tidal volumes prevented alveolar derecruitment induced by 100% oxygen. Finally, the peritonitis per se may have attenuated any putative toxicity of 100% oxygen: Both reduced and increased sensitivities to hyperoxia were reported in animals challenged with lipopolysaccharide, oleic acid, and gastric juice aspiration (48 -50).…”
Section: Discussionmentioning
confidence: 96%
“…a PaO 2 /FiO 2 ratio above 400 in a normal lung). In addition, the association between a worsened oxygen index and a high FiO 2 may not be necessarily due to direct toxicity but maybe atelectasis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, 8 clinical trials have attempted to evaluate the impact of oxygen targets and hyperoxemia on outcome in mechanically ventilated subjects 38,71,[88][89][90][91][92][93] along with 2 meta-analyses. 94,95 Of these, 4 have evaluated the use of so-called "conservative oxygen therapy."…”
Section: Oxygen and Outcomes In Ventilated Patientsmentioning
confidence: 99%
“…In a few cases, excessive F IO 2 has been associated with absorption atelectasis and worsening gas exchange. 38,90,91 However, this typically occurs when F IO 2 ϭ 1.0, not because of need but as part of the study design. In more recent trials, there appears to be a signal related to the duration of ventilation.…”
Section: The Con Summarymentioning
confidence: 99%